Quantum Information Theory for Network Quantum Communication - Loso Judijanto (Yayasan Adra Karima Hubbi, 2025)
The background of this research focuses on the importance of quantum communication in overcoming the challenges of global communication security and efficiency. Using quantum information theory, this study aims to explore the potential of network quantum communication in presenting safer and more efficient solutions. The research methods used combine hands-on experiments and analysis of quantum theory to understand how quantum communication systems can be applied in the real world. The results show that although there are still technical challenges, especially in qubit management and error correction, significant progress has been made in experiments that integrate quantum communication with satellites and optical fibers. These results open up great opportunities for the development of quantum communication technology in practical applications, especially for cryptography and secure transmission of information. The conclusion of this study highlights that despite the many challenges to be faced, this research makes an important contribution in understanding ways to develop and implement stable and efficient network quantum communication. Further research is needed to overcome technical limitations and accelerate the development of this technology on a global scale.